International Students in Non-Anglophone Countries: Challenges and Opportunities - de Wit, Hans; Wang, Lizhou (International Higher Education, 2022)
In studies about international student recruitment and mobility, the emphasis is primarily on South–North mobility to the Anglophone world. But the reality is more diverse. What are the challenges and opportunities of non-Anglophone countries, in particular in the Global South, shifting from mainly being sending countries toward striving to receive international students?